Influence of substitution pattern and enhanced π-conjugation on a family of thiophene functionalized 1, 5-dithia-2, 4, 6, 8-tetrazocines1. (24th September 2015) - Magnan, François; Korobkov, Ilia; Brusso, Jaclyn
<x xml:space="preserve">Abstract</x> The versatile, one-pot synthesis of a series of π-extended 1, 5, 2, 4, 6, 8-dithiatetrazocines is described, along with their optoelectronic and structural properties.